Conceptualization and Problems in the Implementation of Fostered Children's Health Services to Support the Progressiveness of the Child Criminal Justice System in Tangerang Children's Penitentiary - Alfitra Alfitra; Ali Mansur (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The existence of new thoughts rergarding on the fostering function becomes more than an entrapment, but also functioned on social rehabilitation and reintegration of prison-assisted children system that has long been known called a penal system. Protection of children in all activities is conducted to guarantee and protect their rights so they can live, grow, develop and participate optimally according to human dignity and get the protection from violence and discrimination. Although various improvements have been conducted regarding the criminal management for children in prison, such as conditional criminal punishment, parole, and special prosecution institutions, but basically the nature of the penalties and child health services still departs from the principle and the prison system. For this reason, efforts should be made to ensure that youngsters behave according to the existed norms. To achieve this goal, those efforts are required to foster, maintain and improve the welfare of children. This study uses qualitative research method with empirical-normative approach. The result of the study shows that the system of imprisonment and guidance based on Law Number 12 of 1995 concerning Penitentiary, which is accompanied by an institution